PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN RAPAT KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Eny Purwaningsih; Mitfah Sarifani (Melati Institute, 2023)
Exploration of the effect of firm size (FS) and leverage (DAR) on earnings management with independent commissioners meeting (RKI) as the moderating variable is the aim of this study. The use of quantitative and causal methods is the basis of this research which is supported by a population in the form of food and beverage companies listed on the Indonesia Stock Exchange during the 2018-2020 period and purposive sampling technique as the basis for determining the sample. Moderated regression analysis were chosen as data analysis techniques. Based on the results of statistical tests show that firm size (FS) has a positive effect on earnings management, leverage (DAR) has a negative effect on earnings management. Furthermore, the independent commissioner's meeting (RKI) cannot moderate the effect of firm size (FS) on earnings management, and the independent commissioner's meeting (RKI) can weaken the leverage effect (DAR) on earnings management.